(untitled) (Philology, 2024)
This paper aims to examine how beauty has been perceived as a societal construct through the lens of the white and black paradigms, as depicted in Toni Morrison’s novel The Bluest Eye. It explores how this pursuit of the idolized beauty standard, perpetuated by mass media, blurs the lines of self-identity. This study investigates issues of discrimination and identity, examined through the solitary and tragic narrative of Pecola Breedlove, who, from a young age, longs for white skin, blond hair, and blue eyes, thereby subjugating her life to the stereotypes of white supremacy. In light of the politics of racial beauty and identity, the text illustrates how racial discrimination fosters negative perceptions of self and race among Black individuals, driving a yearning to attain whiteness that ultimately contributes not only to their societal disintegration but may also lead to madness.